Facilitate risk management in construction process by using hierarchical risk breakdown structure - Chaher, Zid Chaher; Soomro, Ali Raza (International Journal of Scientific and Research Publication, 2016)
Risk management is an important part of the decision-making process in construction project management, particularly regarding the project’s integration, scope, time, cost, quality, human resources, communications and procurement. Risk management improves the future prospects of a project as it identifies uncertainties and probabilities. However, A lot of analysts and experts have been struggling to define risks by using many analysis and methods where have been applied to define these uncertainties and risks. But eventually, these methods have showed up a weak and sometimes a fatal data missing which may lead to affect directly on the risk management and success of project. In this research paper highlights on one of the most useful and practical method Hierarchal Risk Breakdown Structure which may facilitate to identify and quantify all risks to which the project is exposed so that a conscious decision can be taken on how to manage the risk.